Consumer Behavior on the Policy of Banning the Use of Plastic Bag in Kuantan - Mokhtar, Mazita; AbdulGhani, Airin; Daud, Sarbani; Rizyani Tahir, Ida (KnE Social Sciences, 2019)
By and by, natural issues sway our everyday lives. It is important to battle the difficulties that come as unnatural weather change issues. Among marker components of an Earth-wide temperature, boost is waste created from plastic sacks. Plastic sacks have turned into a significant device for controlling nature, and its impact is tremendous. With expanded ecological issues brought about by plastic sacks throughout the most recent decade, biodegradable plastic packs (BPBs) seem like an ideal arrangement as they are intended to disintegrate totally, without leaving a reasonable impression. Consequently, the fundamental target of this venture is to expand mindfulness among buyers to supplant plastic sacks to BPBs. This is an examination that incorporates a quantitative research way to deal with distinguish key vital elements that impact the utilization of BPB among purchasers. The hypothesis of arranged conduct, by (Ajzen and Maden, 1986) will be utilized in this investigation. As a huge yield, this investigation centers around the standards of green living practices to locate the option of assets that can help accomplish better regular habitat objectives.